2019
DOI: 10.1016/j.biortech.2019.01.085
|View full text |Cite
|
Sign up to set email alerts
|

Garden and food waste co-fermentation for biohydrogen and biomethane production in a two-step hyperthermophilic-mesophilic process

Abstract: A B S T R A C TCo-fermentation of garden waste (GW) and food waste (FW) was assessed in a two-stage process coupling hyperthermophilic dark-fermentation and mesophilic anaerobic digestion (AD). In the first stage, biohydrogen production from individual substrates was tested at different volatile solids (VS) concentrations, using a pure culture of Caldicellulosiruptor saccharolyticus as inoculum. FW concentrations (in VS) above 2.9 g L −1 caused a lag phase of 5 days on biohydrogen production. No lag phase was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Particularly, bioenergy research is increasingly looking for non-edible sources of biomass and for bio-based environmentally friendly processes. The biomass resources from agriculture [3][4][5], forest [6][7][8] and municipal waste [9][10][11] can be converted biologically or thermochemically. However, the biological conversion can be hindered by the presence of low-biodegradable organic matter.…”
Section: Context Challenges and Aimmentioning
confidence: 99%
“…Particularly, bioenergy research is increasingly looking for non-edible sources of biomass and for bio-based environmentally friendly processes. The biomass resources from agriculture [3][4][5], forest [6][7][8] and municipal waste [9][10][11] can be converted biologically or thermochemically. However, the biological conversion can be hindered by the presence of low-biodegradable organic matter.…”
Section: Context Challenges and Aimmentioning
confidence: 99%
“…According to these studies, the highest biogas production could be achieved when the hyperthermophilic pretreatment was combined with thermophilic digestion in a subsequent stage. In contrast, Abbreu et al [16] successfully applied a two-step hyperthermophilic-mesophilic digestion process for the treatment of garden and food waste. The authors reported that hydrogen was produced in the hyperthermophilic stage, whereas methane was generated in the mesophilic step.…”
Section: Introductionmentioning
confidence: 99%
“…Garden and park waste are generated from the maintenance of private gardens and public parks, and represent an economic substrate to produce biohythane (a mixture of hydrogen and methane, usually with 10 to 25% hydrogen in volume) and hydrogen via anaerobic dark fermentation [77,134,135]. In general, we can identify three major components: an organic fraction from garden grass, small bushes containing an undefined organic content and inorganic elements (on a dry matter basis, 0.6% N, 0.1% P, and 1.0% K), and ash, whose content is related to the amount of soil present.…”
Section: Garden Wastementioning
confidence: 99%